Prevalence and Characteristics of Talon Cusp in Deciduous Teeth Among Libyan Children - Aisha Areibi; Mabroukah Imbarak (AlQalam Journal of Medical and Applied Sciences, 2025)
The talon cusp is a relatively rare dental developmental anomaly characterized by cusp-like projections, usually observed on the lingual surface of the affected tooth. To determine the prevalence of talon cusps in Libyan children with respect to sex, jaws, and dental localization to determine the relation between sex and this anomaly. It was performed by clinical examination of the patients for the presence of talon cusps. Examination of 2000 Libyan children aged four to six years. Talon cusps were observed in 42 patients. Thus, the prevalence of talon cusp was 2.1 %. In addition, the results highlight a significant predilection for anomalies in the maxillary arch. In this study, the maxillary canines were the most commonly affected teeth in the mouth, with no gender variation. The prevalence figure for primary maxillary canine talon cusp was so high that it may be appropriate to consider this anomaly as being characteristic of the Libyan children’s primary dentition. Clinicians should be aware of potential complications that may occur with talon cusps. It is important to recognize that the management of talon cusps may require a multidisciplinary approach and should be considered during treatment planning.